TRUST MEREK DI ERA AI: MEDIASI NIAT BELI GENERASI Z DAN VIRTUAL INFLUENCER - Anggraeni, Vilma Dewi (POLITEKNIK LP3I JAKARTA, 2026)
The contemporary digital marketing landscape is defined by the acceleration of Artificial Intelligence (AI) technology, giving rise to the Virtual Influencer (VI) phenomenon and the massive adoption of AI-Generated Content (AIGC). This shift creates new tensions, particularly in cultivating consumer trust among Generation Z, an audience known for valuing authenticity. This study aims to empirically test: (1) the influence of Virtual Influencers on Generation Z consumers' Brand Trust, (2) the influence of AI-Generated Content on Generation Z consumers' Purchase Intention, and (3) the mediating role of Brand Trust within these relationships. Employing a quantitative approach utilizing a Generation Z sample, the study results indicate that the adoption of Virtual Influencers faces significant challenges in establishing Brand Trust due to skepticism surrounding authenticity and the critical need for AI transparency. Conversely, AI-Generated Content was found to have a direct, positive, and significant influence on Purchase Intention, especially when the content is perceived as having high credibility and informativeness. The most crucial finding confirms that Brand Trust acts as a full and vital mediating variable; the influence of both Virtual Influencers and AI-Generated Content on Generation Z's Purchase Intention is only effectively realized after these variables successfully build and sustain brand confidence. The practical implications emphasize that brands must prioritize strict AI transparency ethics and ensure the quality of AIGC focuses on information to convert digital exposure into tangible purchasing actions.